The concept of an integrated Islamic curriculum and its implications for contemporary Islamic schools - Yaacob, Solehah@Nik Najah Fadilah; Embong, Rahimah (2008)
The Emergence of `Islamic Education Movement` is a response to the `secularization of education` faced by the ummah (muslim people) all over the world; in the sense that the `traditional Islamic Sciences` which are rooted in Islamic sources i.e. al-Qur’an (the Holy Book) and as-Sunnah (Tradition of the prophet) have been marginalized. Subsequently, Muslim scholars have made serious endeavors to define the concept of Islamic education and then to develop a genuine Islamic education model based on `the basic tenets of aqidat al-tawheed` (principle of faith). This reformation of education has envisioned to produce the new Muslim generation, which is capable of fulfilling its role as khalifatullah (vicegerent of God)i.e. responsible for the development and maintenance of civilization and its resources. In another word, Islamic education is obliged to deal with the overall development of the individual, i.e. spiritual, intellectual, imaginative, physical, scientific, linguistic,both individually and collectively. In sum, the ultimate of Islamic education is in `the realization of complete submission to Allah on the level of the individual, the community and humanity at large.